Optimazing Performance Efficiency Ratio for Network Planning in 5g Using Millimeter-Waves - Kaschel-Carcamo, H; Adasme-Soto, P; Castillo-Del Barrio, E; Cordero-Leiva, S (Institute of Electrical and Electronics Engineers Inc., 2024)
This article presents two mathematical optimization models to solve problems related to designing and planning 5G wireless communications networks using millimeter wave frequency spectrum. Firstly, a fractional binary programming model is proposed to obtain an optimal performance efficiency ratio to maximize users over the whole latency. This allows the planning of 5G networks operating in the Millimeter Wave (mmWave) frequency spectrum. Starting from a set of restrictions in the first model, we obtain linear and quadratic models. In addition, the binary variables for a 5G network are defined considering a random distribution of the base stations in an area of 1 km 2. Together with the above, we establish a constraint of the model that guarantees that at least each user is covered by one active base station at a predefined distance. The second proposed model is a quadratic model that maximizes user coverage, allowing efficiency to be established in a 5G network. This is achieved by excluding the linear restrictions applied to the first linear model. Our models assume the existence of Line-of-Sight (LOS) for links between users and base stations. Finally, we consider instances composed of 30 to 50 base stations, and 500 to 3000 users, using distances of 200 and 250 ms. Our numerical results show that the proposed models can optimally solve all the instances in a short CPU time. © 2024 IEEE.